New‐onset cognitive dysfunction impairs the quality of life in patients after liver transplantation. Issue 7 (26th May 2014) - Tryc, Anita Blanka; Pflugrad, Henning; Goldbecker, Annemarie; Barg‐Hock, Hannelore; Strassburg, Christian P.; Hecker, Hartmut; Weissenborn, Karin
<x xml:space="preserve">Abstract</x> Patients after orthotopic liver transplantation (OLT) may show cognitive dysfunction. To date, it has not been clear whether this dysfunction is due to residual hepatic encephalopathy (HE) or new‐onset cognitive disturbances. Just as little is known about the course and clinical significance. In this prospective, observational study, 50 patients on the waiting list for OLT were examined in an outpatient setting before OLT and 6 and 12 months after OLT with the Psychometric Hepatic Encephalopathy Score, the Inhibitory Control Test, and the critical flicker frequency for the diagnosis of HE; in addition, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) was used as a tool for the measurement of global cognitive function. The Short Form 36 health survey was used to assess health‐related quality of life. Twelve months after OLT, cognitive dysfunction characteristic of HE had resolved, but a secondary cognitive decline became apparent and had features different from those known with HE. Approximately 70% of the patients deteriorated in at least 1 cognitive domain of RBANS. This cognitive decline was related to neither a history of HE nor a history of alcohol abuse, but it was accompanied by a decline in the quality of life. In conclusion, OLT improves HE but is frequently followed by new‐onset cognitive dysfunction, which can interfere with the quality of life. Liver Transpl 20:807–814, 2014. © 2014 AASLD.